Lightweight expanded aggregates from the mixture of waste automotive plastics and clay. (1st August 2017) - Liu, Peiyao; Farzana, Rifat; Rajarao, Ravindra; Sahajwalla, Veena
Highlights: Light weight aggregates were manufactured from waste automotive plastics and clay. 39.5% higher porosity and 28.5% lower bulk density was achieved compared to clay. This innovative and eco-friendly approach could help reduce auto plastics in landfills. Abstract: Significant amount of waste associated with end of life vehicles enter waste stream each year and are usually disposed of in landfill, creating an environmental burden. Recycling automotive waste is very tedious and difficult due to its heterogeneous composition and nature. It is critically required to develop a solution to recycle and reuse these potential resources. In this paper, a novel recycling approach is established to produce lightweight aggregate by incorporating automotive shredded residual (ASR) plastics into clay at 1200 °C. The physical properties of lightweight aggregate such as bulk density, porosity and water absorption have been investigated. ASR plastics as pore-forming or gas releasing agent increased the porosity of the clay mixture. Incorporation of 2 wt% of ASR plastics into clay composite lead to a benefit of approximately 30% bulk density decrease and 40% porosity increase compared to the reference clay material used in this study. The obtained superior lightweight and porous aggregate products by using ASR plastics can be used in thermal insulation materials and also as substrates in soilless cultivation. This innovative approach could also help reduce the volume of autoplastics in landfills and could be a potential replacement of conventional additives in manufacturing composite materials for building applications.